Chemical Peels - Jackson, Adrianna (Facial Plastic Surgery, 2014)
Chemical peels are a method of resurfacing with a long-standing history of safety in the treatment of various skin conditions. This article reviews the classification of different chemical agents based on their depth of injury. The level of injury facilitates cell turnover, epidermal thickening, skin lightening, and new collagen formation. Preprocedural, periprocedural, and postprocedural skin care are briefly discussed. To select the appropriate chemical peel, the provider should evaluate the patient's expectations, medical history, skin type, and possible complications to determine the best chemical peel to achieve the desired results. Patients with Fitzpatrick skin types IV to VI have increased risk of dyspigmentation, hypertrophic, and keloid scarring. These individuals respond well to superficial and medium-depth chemical peels. Advances in the use of combination peels allow greater options for skin rejuvenation with less risk of complications.
Keywords: chemical peel; resurfacing; photodamage; pigmentation; rhytides